PENYULUHAN KEBERSIHAN LINGKUNGAN SEBAGAI UPAYA PENCEGAHAN PENYAKIT DEMAM BERDARAH DENGUE DI DESA ARU IRIAN KECAMATAN MOROTAI SELATAN BARAT - Cabu, Roberto; Fika, Elfira Christin (HIRONO : Jurnal Pengabdian Masyarakat, 2024)
The aim of implementing outreach in Aru Irian Village is to increase community knowledge about maintaining environmental cleanliness and knowing the causes, behavior of dengue mosquitoes and how to prevent dengue fever. The activity was carried out in Aru Irian Village, South West Morotai Sub-district, with the implementation stages of the activity divided into 3 stages, namely preparation, counseling and evaluation. The evaluation results show that there has been an increase as indicated by an increase in knowledge about dengue fever by 64%, public knowledge about the Aedes Aegepti mosquito has increased by 64%, knowledge of mosquito breeding places has increased by 28% and knowledge of dengue prevention has increased by 76%.